EVALUATION OF THE IMPLEMENTATION OF A SCIENTIFIC APPROACH IN ISLAMIC ELEMENTARY SCHOOL AQIDAH AKHLAK SUBJECTS - Wiyanti, Erna Tri; Mujiburrohman, M (Proceeding of International Conference of Islamic Education, 2023)
This study aims to find out how the process of evaluating the implementation of learning with a scientific approach in the Aqidah Akhlak subject at Madrasah Ibtidaiyah. The method used in this research is descriptive qualitative. Qualitative descriptive research aims to describe, describe, explain, explain and answer in more detail the problems to be studied by studying as much as possible an individual, a group or an event. The subjects of this research were aqidah morals teachers and fifth grade students at the Islamic Elementary School in Klego Boyolali District. In Klego subdistrict there are 13 Villages/Kelurahan. Of the 13 villages there are 18 madrasah ibtidaiyah. Data obtained through observation, interviews and documentation. Data validation techniques in this study are technique triangulation and source triangulation. While data analysis is divided into several stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the making of lesson plans has led to a scientific approach with components of lesson plans that have implemented a scientific approach proven in the core learning activities to observe, ask questions, gather information, try to reason and communicate.